PEMAHAMAN MASYARAKAT KOTA BANDA ACEH TENTANG PROTOKOL KESEHATAN DARI MEDIA MASSA - Fitri Meliya Sari; Almukarramah Almukarramah; Ainal Fitri (Jurnal Komunikasi dan Kajian Media, 2021)
Abstract: During the Covid 19 pandemic, many new regulations were established, both the implementation of the New Normal Era and the Health Protocol. This regulation applies throughout the world, including in Indonesia and Aceh. The mass media has a special role in disseminating information about health protocols in the new normal era. Seeing this, the researchers conducted research on how the Acehnese people understood the application of health protocols in the new normal era that had been reported or informed through mass media, both printed media, online media and even electronic media. In Banda Aceh, social sanctions are imposed for those who violate health protocols. This study uses qualitative research methods with data collection techniques using google form where the researcher also carries out a social distancing policy in accordance with the regulations in the new normal era. The result of this research is that the people of Banda Aceh understand about the Health Protocol regulations and how they are implemented, as well as the sanctions that will be imposed when they violate the regulations, but even though they understand this, there are still many Banda Aceh people who are subject to sanctions.Keywords: Mass Media, Health Protocol, New Normal, Banda Aceh City